2018
DOI: 10.1002/pros.23489
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast‐derived factors promote metastatic potential in human prostate cancer cells, in part via non‐canonical transforming growth factor β (TGFβ) signaling

Abstract: These findings suggests that factors secreted from osteoblasts, including TGFβ, can induce several cellular traits involved in metastatic potential of PC-3U cells, further strengthening the role for bone cells to promote metastatic tumor cell behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It is becoming increasingly evident that osteoblasts in the bone microenvironment play vital roles in cancer cell progression in bone [19,[32][33][34][35][36]. According to one study that used dynamic longitudinal imaging and intravital microscopy, osteoblast cells in the endosteal niche suppressed multiple myeloma cancer cell proliferation and maintained bone-disseminated cancer cells in a dormant state during early disease [104].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is becoming increasingly evident that osteoblasts in the bone microenvironment play vital roles in cancer cell progression in bone [19,[32][33][34][35][36]. According to one study that used dynamic longitudinal imaging and intravital microscopy, osteoblast cells in the endosteal niche suppressed multiple myeloma cancer cell proliferation and maintained bone-disseminated cancer cells in a dormant state during early disease [104].…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly evident that osteoblasts in the bone microenvironment play vital roles in cancer cell attraction [34,35], maintenance [33], and survival [19,32,36] during cancer progression in the bone. It was demonstrated that osteoblast-derived TGF-beta increased PC-3U prostate cancer cell migration [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previews secrete factors such as TGFb, which are deposited into the mineralized bone matrix and can induce the metastatic potential of prostate cancer cells (Karlsson et al, 2018). Osteoblasts secrete factors (Kinder et al, 2008) and also differentiate into osteocytes, both of which can initiate osteoclastogenesis.…”
Section: Cell Metabolismmentioning
confidence: 99%
“…Bone sialoprotein, which is a major glycoprotein, is regulated by TGF-β through β-catenin signaling [31]. Recently, it has also been reported that osteoblast-derived soluble factors, including TGF-β, indeed promote metastatic potential in prostate cancer cells, and the effect by TGF-β is, at least partly, mediated by noncanonical TRAF6-dependent signaling [32]. …”
Section: Tgf-β Exists In Bone Tissue and Is Implicated In Bone Metmentioning
confidence: 99%